Drivers of Subsidiary Competences: The Case of Japan - Giroud, Axèle; Ha, Yoo; Marukawa, Kazuyuki; Iguchi, Chie (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2021)
This paper addresses drivers behind whether foreign subsidiaries located in Japan possess single or multiple competences. We use an original database compiled by means of survey amongst foreign subsidiaries operating in the Japanese manufacturing sector. Results show that subsidiaries predominantly possess a sales & marketing competence, but some also have multiple competences in business functions and/or technological competences. Subsidiaries with greater autonomy, significant internal network relationships, and external business networks are more likely to demonstrate a wider range of key competences. The paper provides novel contributions, demonstrating that drivers show differences in explaining various competences, and exploring subsidiary competences in the unique Japanese host environment.